ANALISIS POLITIK HUKUM KETENAGAKERJAAN TERHADAP UNDANG-UNDANG PERLINDUNGAN TENAGA KERJA DI LUAR NEGERI PADA PENERAPAN FAIR TRIAL KASUS PEMBEBASAN SITI AISYAH - Yanto Irianto (Jurnal De Jure Muhammadiyah Cirebon, 2022)
Article 9 of the General Declaration of Human Rights states that: "No one may be arbitrarily arrested, detained or exiled." The government succeeded in freeing Indonesian citizen from Serang, Banten, Siti Aisyah from Malaysian law, Monday (11/3/2019). This case is related to the alleged murder of Kim Jon Nam, the half-brother of North Korean leader Kim Jong-Un. Siti was released after the prosecutor dropped the charges during the trial. The Minister of Law and Human Rights, Yasonna Laoly stated, the release of Siti Aisyah was proof of the presence of the government for Indonesian citizens. In order to avoid a double standard between the Government's efforts to encourage the implementation of a fair trial and the abolition of prosecution for death sentences experienced by Indonesian citizens abroad and those tried in Indonesia, the ICJR recommended President Jokowi to order the Attorney General to carry out a moratorium on the prosecution of sentences. death and stop the execution of the death penalty considering the implementation and standards of fair trial in Indonesia are still not running well. Keywords: Freedom; Fair Trial; Justice.